Informacijsko komunikacijske tehnologije u europskom istraživačkom prostoru - Mesarić, Josip (Array, 2009)
Development and implementation of ICT become the basis of world competitiveness of single European socio-economic space and this development is managed by highest level of socio-political decision making in European Union. Since the European geopolitical map has changed considerably in the last two decade, and became heterogeneous in levels of economic development and capabilities for research, development and implementation of ICT, the need for empowering of less developed regions (countries) has emerged on one side as well as fostering the leadership, excellence and collaboration of developed regions on the other side. Due to these goals, considerable funds were and are planned to be invest in ICT research and development in EU. Based on number of participants and leadership in some ICT projects of European research programs (subprograms), publically available in CORDIS database, the levels of ICT research and development capacities of European countries and some candidate countries are investigated. The results are analyzed in contextual framework of European ICT projects and some socio-economic factors of particular country in order to assess differences and future capacities for ICT research and development.